Rethinking Molecular Mimicry in Rheumatic Heart Disease and Autoimmune Myocarditis: Laminin, Collagen IV, CAR, and B1AR as Initial Targets of Disease - Root-Bernstein, Robert (Frontiers in Pediatrics, 2014)
Rationale: Molecular mimicry theory (MMT) suggests that epitope mimicry between pathogens and human proteins can activate autoimmune disease. Group A streptococci (GAS) mimics human cardiac myosin in rheumatic heart disease (RHD) and coxsackie viruses (CX) mimic actin in autoimmune myocarditis (AM). But myosin and actin are immunologically inaccessible and unlikely initial targets. Extracellular cardiac proteins that mimic GAS and CX would be more likely. Objectives: To determine whether extracellular cardiac proteins such as coxsackie and adenovirus receptor (CAR), beta 1 adrenergic receptor (B1AR), CD55/DAF, laminin, and collagen IV mimic GAS, CX and/or cardiac myosin or actin. Methods: BLAST 2.0 and LALIGN searches of the UniProt protein database were employed to identify potential molecular mimics. Quantitative ELISA was used to measure antibody cross-reactivity. Measurements: Similarities were considered to be significant if a sequence contained at least 5 identical amino acids in 10. Antibodies were considered to be cross-reactive if the binding constant had a Kd less than 10-9 M. Main Results: GAS mimics laminin, CAR and myosin. CX mimics actin and collagen IV and B1AR. The similarity search results are mirrored by antibody cross-reactivities. Additionally, antibodies against laminin recognize antibodies against collagen IV; antibodies against actin recognize antibodies against myosin, and antibodies against GAS recognize antibodies against CX. Thus, there is both mimicry of extracellular proteins and antigenic complementarity between GAS-CX in RHD/AM. Conclusions: RHD/AM may be due to combined infections of GAS with CX localize at cardiomyocytes may produce a synergistic, hyperinflammatory response that cross-reacts with laminin, collagen IV, CAR and/or B1AR. Epitope drift shifts the immune response to myosin and actin after cardiomyocytes become damaged.